Postural Adjustments and Biomechanics During Gait Initiation and Obstacle Negotiation: A Comparison Between Akinetic-Rigid and Hyperkinetic Parkinson’s Disease - Casal, Marcela Zimmermann; Peyré-Tartaruga, Leonardo Alexandre; Zanardi, Ana Paula Janner; Ivaniski-Mello, André; Alves, Lucas de Liz; Haas, Aline Nogueira; Martinez, Flávia Gomes (Frontiers in Physiology, 2021)
Background: Individuals with Parkinson's disease (PD) exhibit different combinations of motor symptoms. The most frequent subtypes are akinetic-rigid (AK-R) and hyperkinetic (HYP). Motor symptoms, such as rigidity and bradykinesia, can directly affect postural adjustments and performance in daily tasks, like gait initiation and obstacles negotiation, increasing the risk of falls and functional dependence. Objective: To compare postural adjustments and biomechanical parameters during the gait initiation and obstacle negotiation of people with AK-R and HYP PD and correlate with functional mobility and risk of falls. Methods: Cross-sectional study. Thirty-three volunteers with PD were divided into two groups according to clinical motor manifestations: AK-R (n=16) and HYP (n=17). We assessed the anticipatory (APA) compensatory (CPA) postural adjustments analyzing kinematic, kinetic and, electromyographic parameters during the gait initiation and obstacle negotiation tests. We applied independent T-tests and Pearson correlation tests for comparisons and correlations, respectively (α=.05). Results: In the APA phase of the gait initiation test, compared to the functional HYP group, the AK-R group showed shorter time for single support (p=.01), longer time for double support (p=.01) accompanied by a smaller first step (size, p=.05; height, p=.04) and reduced muscle activation of obliquus internus (p=.02). Similarly, during the first step in the obstacle negotiation test, the AK-R group showed less step height (p=.01) and hip excursion (p=.02), accompanied by a reduced mediolateral displacement of the center of pressure (p=.02) during APA, and activation of the gluteus medius (p=.02) and the anterior tibialis (p=.04) during CPA in comparison with HYP group. Conclusion: The findings suggest that people with AK-R present impaired postural adjustments during gait initiation and obstacles negotiation compared to hyperkinetic PD. Based on defined motor symptoms, the proposition presented here revealed consistent postural adjustments during complex tasks and, therefore, may offer new insights onto PD motor evaluation and neurorehabilitation.